POTENSI LIMBAH SAGU (Metroxylon sp.) DI KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI SEBAGAI SUBSTRAT PENGHASIL BIOGAS - Anuar, Khaidir; Zul, Delita; ', Fitmawati (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Biogas is one of alternative energy sources that fulfills future fuel needs. This studyaimed to analyse the potency of sago waste as fermentation substrate for biogasproduction. This research was done experimentally by employing sago waste materialsobtained from Sago Factory Nambus River from District West Tebing Tinggi Sub-province Meranti and fresh cow rumen liquid was obtained from slaughterhouse inPekanbaru. The biogas volume was calculated by measuring the volume of water thatwas pushed every 3 days, where the volume of water driven was proportional to thevolume of biogas produced. The bacterial cell numbers was counted using plate countmethod employing Nutrient Agar (NA). The substrate fermentation temperature and pHwere measured every 3 days. The highest biogas volume was produced by fermenter III(45760 ml) containing solid sago waste, liquid sago waste, and rumen liquid with ratio 1: 1 : 1 and the lowest was produced by fermenter II (1600 ml). The total bacterialinvolved in biogas production ranges from 1,87x10 5 – 2,87x10 8 CFU/ml samples. Thetemperature and pH of substrate fermetation was relatively constant during biogasproduction. The results showed that sago waste is potential as substrate for biogasproduction.